Sociolinguistic Issues in CSOL Testing - Udier, Sanda Lucija (2009)
The aim of this paper is to show sociolinguistic and extralinguistic issues in testing Croatian language for non native speakers. It presents Croatian legislation on it and shows it's organisational and glotodidactical side.